2014
DOI: 10.1155/2014/840379
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofMomordica charantiaL. on the Blood Rheological Properties in Diabetic Patients

Abstract: An evaluation of the rheological properties and the effects of Momordica. charantia L. (M. charantia) nanoparticles and polyethylene glycol (PEG) microspheres adsorbed with M. charantia nanoparticles on the blood of hyperglycemic patients is presented. Blood samples were collected according to glycemic status: normoglycemic (N = 56) and hyperglycemic (N = 26). General and hematological characteristics were determined. Blood rheological parameters were determined at room temperature and under a temperature scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 41 publications
1
34
0
1
Order By: Relevance
“…The study showed that regular consumption of these tablets associated with positive effects in glucose, cholesterol, HDL, LDL, triglyceride levels and had beneficial effects on glucose tolerance [55]. Furthermore, nanoparticles of extract of M. charantia and its adsorption on polyethylene glycol (PEG) microspheres are considered as an alternative treatment of diabetes [56]. Considering all these facts, it can be concluded that Momordica has potential anti-diabetic properties, which may suggest the inclusion of this plant in anti-diabetic regimens.…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…The study showed that regular consumption of these tablets associated with positive effects in glucose, cholesterol, HDL, LDL, triglyceride levels and had beneficial effects on glucose tolerance [55]. Furthermore, nanoparticles of extract of M. charantia and its adsorption on polyethylene glycol (PEG) microspheres are considered as an alternative treatment of diabetes [56]. Considering all these facts, it can be concluded that Momordica has potential anti-diabetic properties, which may suggest the inclusion of this plant in anti-diabetic regimens.…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…As for instance, liquid and translucent emulsions with long-term stability and appropriate for different applications generally exhibit Newtonian behavior with constant viscosity for a wide range of shear rate (Rojas et al, 2009;Acharya and Hartley 2012;Ribeiro et al, 2015;Cotrim et al, 2016). According to the literature, viscosity is largely influenced by modified-release systems associated with change of temperature França et al, 2014). In this report, the prepared formulations of Brazil nut oil and LMS presented Newtonian profile and no change in the hysteresis area.…”
Section: Resultsmentioning
confidence: 58%
“…Several candidate functional materials have been evaluated by assessing the biocompatibility and interaction with human cells. 14,26 The data suggest that the acid and cement treatments applied to the metal surfaces resulted in a material with low cellular toxicity, which can be used to improve the application of cemented implant prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…The rheological parameters were measured using a Modular Compact Rheometer -MCR 102 (Anton Paar ® Germany GmbH, Ostfildern, Germany) according to França et al 14 In all of the experiments, the implant surfaces treated or untreated with phosphoric acid were placed in 600 µL human blood and put on the reading plate surface, and the excess sample was removed. Readings were taken with continuous control of the gap measurement with the supported TruGap™ of 0.099 mm.…”
Section: Rheological Characterization Of the Implant Surfacesmentioning
confidence: 99%